A novel study on COF-based semi-solid electrolyte for spinel LiNi0.5Mn1.5O4 targeting transition metals migration. (15th January 2023) - Zhao, Hong; Ren, Yaqi; Bo, Xiangkun; Si, Liping; Wei, Zhaohuan; Daoud, Walid A.
Abstract: Cobalt-free battery is one of the development trends of lithium-ion batteries. High-voltage LiNi0.5 Mn1.5 O4 (LNMO) with high theoretical energy density is one of the most promising Co-free cathode materials in the further. However, the side reaction between the LNMO electrode and electrolyte at high voltage or high temperature and the corresponding by-products (e.g. Mn 2+ /Mn 3+ and Ni 2+ ) severely deteriorate the battery performance. In this work, an anionic covalent organic framework (COF)–based semi-solid electrolyte was constructed by synthesizing a free-standing COF film with a small amount of liquid electrolyte. Further, the experimental results proved that the cycling and C-rate performance of LNMO battery is improved by using the semi-solid electrolyte. This can be proposed that the anionic COF is capable of absorbing strongly the Mn 3+ /Mn 2+ and Ni 2+ through Coulomb interaction, restraining their destructive migration to the anode. Therefore, this work will be beneficial to the commercialization of LNMO cathode material. Graphical abstract: In this work, an anionic COF–based semi-solid electrolyte was constructed. The COF–based semi-solid electrolyte can suppress the transition metals (by-products) from migrating to the anode through Coulomb interaction, finally benefitting the full cell performance. Image, graphical abstract